Nutritional status evaluation and nutrient intake in adult patients with pulmonary tuberculosis and their contacts - Campos-Gongora, Eduardo; López-Martínez, Julieta; Huerta-Oros, Joselina; Arredondo-Mendoza, Gerardo I; Jiménez-Salas, Zacarías (The Journal of Infection in Developing Countries, 2019)
Introduction: Malnutrition is a common status in patients with tuberculosis (TB). Because TB is disseminated through the sputum of infected persons, individuals who maintain relations with a TB patient are at high risk of infection; this risk is greater when contacts present an inadequate nutritional status. The aim of this work was to analyse and compare the nutritional status and macro and micronutrient intake of TB patients and their household contacts. Methodology: A cross-sectional study was carried out in TB patients from Nuevo Leon, México, and their household contacts. Thirty-nine patients diagnosed with TB and 62 contacts were evaluated. Anthropometric evaluation was performed considering weight, height, body mass index (BMI) and waist-hip ratio (WHR); nutrient intake was evaluated by applying 24-hour dietary recalls. Results: According to anthropometric assessment, the study population showed a greater trend towards being overweight and obese; 62% of TB patients and contacts had this type of malnutrition, while only 8% of individuals were undernourished. A greater tendency towards malnutrition was observed in the TB patient group. Conclusions: TB patients and their contacts presented as overweight and obese. Both groups showed similar patterns in macro and micronutrient intake. Implications of deficiencies in the intake of these nutrients are discussed on the basis of their effects on individual health.